Comportamento sócio-sexual e de manutenção de touros nelore durante a estação de monta - Costa-e-Silva, E. V.; Sereno, J. R. B.; Vasconcelos, J. T.; Zúccari, C. E. S. N.; Costa, M. J. R. Paranhos da [UNESP] (SciELO Espana/Repisalud, 2010)
Changes in the bull: cow proportion in natural breeding have been proposed, but there are not evaluations about the effect of these changes in the behaviour of Nellore bulls. The objective of this study was to test the hypothesis that the increase of sexual activity of Nellore bulls, due to the highest heat incidence (HHI), changes the time of general activity of those animals depending on their social status in the group. Six Nellore bulls were distributed in three groups: one bull in a single-sire breeding group (1bull:60cows) and two in multiplesire breeding groups - one with 2 bulls and 120 cows (cycling naturally) and the other group with 3 bulls and 180 females, 50 of which were synchronised. The behaviour of these animals was recorded during 120 hours, using continuous and direct observation with animal focal sampling. The dominance order influenced the time spent with sexual activities. Bulls under high heat incidence presented the largest sexual activities and the smaller grazing, agonistic interactions and other activities, there was no difference in rumination.
Social hierarchy in nellore bulls and sexual and maintenance activities during breeding season
Keywords: Bos indicus; Grazing; Rumination; Social dominance; Zebu bulls; Animalia